Application of process modeling to the daily task of public school teachers - Pérez Jiménez, Juan Diego (Avances en Supervisión Educativa, 2009)
High quality in education is one of the main issues in present day society. Until now  teaching methods and lesson planning have been the core of  teachers daily  work. However, if we consider education as a public service we must improve current schools management as well.  This review is focused on out -of the- classroom  tasks involved in the teaching activity, so as to present certain quality standards efficiency references.His scope sometimes may be interfered by certain difficulties along the way such as the bulk of written legislation framework. In order to overtake this situation  we suggest to use modeling process techniques as the ones used in business companies sectors BPMN (Business Process Management Notation).  In this articles two best practices models are explained: "the Head of the Department election process" and  "Drop-out prevention action plan for tutors or mentors".